Understanding Migration Factors in Modern Life (Eurasian Journal of Humanities and Social Sciences, 2023)
What is Migration? Why people are migrating a lot these days? Here I will mention some factors that urge people to migrate. In the modern world, migration has become a pervasive and complex phenomenon, shaped by a multitude of interconnected social, political, economic, and environmental factors. This article aims to provide an overview of the key drivers of migration in contemporary society, shedding light on the intricate web of influences that propel individuals and communities to relocate.